(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
The article presents data from studies on the organoleptic evaluation of freeze-dried apricot products. In particular, freeze-drying technology and primary processing processes have a significant impact on the organoleptic properties of apricot products.